Learning Inclusion in a Digital Age Belonging and Finding a Voice with the Disadvantaged - Dobson, Stephen; Svoen, Brit; Agrusti, Gabriella; Hardy, Pip (Sustainable Development Goals Series, 2024)
This open access book considers how inclusive learning, wellbeing and active citizenship can be encouraged, taught, learnt, and supported in a digital world. The book poses and seeks to address three questions: How can governments and intergovernmental organisations support learning inclusion and active citizenship? How can the education sector and public/private enterprises support learning inclusion and active citizenship? How can professionals and communities work with vulnerable adults who are disadvantaged in a participatory, empowering manner? The Examples discussed in the book draw on the experiences of adult refugees and migrants, as well as people who may experience disadvantage and/or discrimination as a result of their social, economic, political, cultural, religious, physical, mental, age or gender-related status. One methodological pillar in this work is the development of skills in digital storytelling and digital storiescreation for personal, community and professional purposes. Conceptually and of interest for researcher and policy makers at local, national and transnational levels, this book brings together a number of related concepts to generate innovative understanding and practices of applied relevance in the age of the pandemic and its aftermath.